2015
DOI: 10.7763/ijesd.2015.v6.562
|View full text |Cite
|
Sign up to set email alerts
|

Biodiesel Production from Castor Oil under Subcritical Methanol Conditions

Abstract: Abstract-Biodiesel is a potentially sustainably renewable fuel for diesel engines; transesterification is the most used method to produce it and high quality vegetable oils are the most usual raw material. Non-edible vegetable oils such as castor oil can provide an alternative feedstock. In this work biodiesel was obtained by transesterification of castor oil with subcritical methanol; the reaction was carried out in an hermetic reactor at temperatures higher than methanol boiling point and with a small amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 32 publications
2
9
1
Order By: Relevance
“…The density of palm oil sludge used for the transesterification reaction was 976 kg/m 3 . The results obtained are within the range reported in the literature (0.9625 g / ml and 0.9772 g / ml) [38]. Comparing this literature value with the density values of palm oil sludge in this research work, we concluded that there is no significance difference with values reported in the literature.…”
Section: Fig 4 Sample Of Biodiesel Produced From Palm Oil Sludge (Pos)supporting
confidence: 86%
“…The density of palm oil sludge used for the transesterification reaction was 976 kg/m 3 . The results obtained are within the range reported in the literature (0.9625 g / ml and 0.9772 g / ml) [38]. Comparing this literature value with the density values of palm oil sludge in this research work, we concluded that there is no significance difference with values reported in the literature.…”
Section: Fig 4 Sample Of Biodiesel Produced From Palm Oil Sludge (Pos)supporting
confidence: 86%
“…However it is always desired to reduce the severity of the reaction conditions attached [13]. A much milder subcritical methanol have been the replacement for many reactions due to its high solubility in many organic and petroleum oils and feedstock [15,21,22] Here subcritical conditions of methanol have shown 59% TAN reduction at a temperature of 210°C and a reaction time of 150 min, which is comparatively higher than the results achieved by previous researchers at this temperature and time condition. Prolonging the reaction time further does not affect the TAN reduction.…”
Section: Tan Reductioncontrasting
confidence: 44%
“…>350°C and 10 MPa, respectively [13,14]. To reduce the severity of reaction conditions subcritical methanol can be an alternative as many processes have shown high conversion of free fatty acids into biodiesel using subcritical methanol [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a new type of chemical, the so-called ionic liquids (ILs), and non-catalysed routes under supercritical conditions have gained attraction among researchers [28][29][30][31]. Even though both strategies have been successfully performed on a laboratory scale, their industrial acceptance and application are still limited due to their high capital and operational cost, non-conformity of the recovery methods, low reusability of ILs, and several technical and operational challenges, including the requirement of heating instrument and high-pressure vessels resulting in high energy demand [32][33][34][35][36].…”
Section: Biodiesel Production Routesmentioning
confidence: 99%